# Solve for z -3(z-4)+5z=6z-5

-3(z-4)+5z=6z-5
Simplify -3(z-4)+5z.
Simplify each term.
Apply the distributive property.
-3z-3⋅-4+5z=6z-5
Multiply -3 by -4.
-3z+12+5z=6z-5
-3z+12+5z=6z-5
2z+12=6z-5
2z+12=6z-5
Move all terms containing z to the left side of the equation.
Subtract 6z from both sides of the equation.
2z+12-6z=-5
Subtract 6z from 2z.
-4z+12=-5
-4z+12=-5
Move all terms not containing z to the right side of the equation.
Subtract 12 from both sides of the equation.
-4z=-5-12
Subtract 12 from -5.
-4z=-17
-4z=-17
Divide each term by -4 and simplify.
Divide each term in -4z=-17 by -4.
-4z-4=-17-4
Cancel the common factor of -4.
Cancel the common factor.
-4z-4=-17-4
Divide z by 1.
z=-17-4
z=-17-4
Dividing two negative values results in a positive value.
z=174
z=174
The result can be shown in multiple forms.
Exact Form:
z=174
Decimal Form:
z=4.25
Mixed Number Form:
z=414
Solve for z -3(z-4)+5z=6z-5

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top